Reparación de heridas de piel y mucosas - Kurzer-G., Erika Liliana; Kurzer-S., Alberto (Revista Facultad de Odontología Universidad de Antioquia, 2018)
The ability to heal wounds by forming-scar tissue is essential for the survival of alllugher species Wounds can be lifethreatenin& commonly affect functional ability, and virtually always compromise appearence. Over the past years therehas been renewed Interest in the basic components of the wound healing-process and how the different steps interact with each other. Surgeons and dentists, perhaps more than any other member of the health team, should have an in-depth knowledge of this processes ilhe or she is to wisely treathis or her patients. This article updates presentIcriowledge of the mechanisms involved in tissue repair, such as: hemostasis, inflamma tion, mesenchyrnal cell migration and proliferation, revasadarization, epithelialization, contraction, collagen production and lysis and remodeling. This various functions involved in the healing process are all orchestrated by cytokines and other mediators of cellularfunction.